Periodontal Conditions in Patients with Osteoporosis - Yoshinari, Nobuo; Hashimoto, Masanori; Nagira, Tamaki; Ozawa, Akira; Suzuki, Hideto; Ohshima, Yasunari; Inagaki, Koji; Fujishiro, Haruyoshi; Noguchi, Toshihide; Takigawa, Toru (Nihon Shishubyo Gakkai Kaishi (Journal of the Japanese Society of Periodontology), 1996)
The aim of the present study was to analyze the possible relationship between osteoporosis and the degree of periodontal disease in postmenopausal women. Thirty-five female patients with osteoporosis (group O, mean age 63.0±1.5) and 20 normal women with periodontitis (group P, mean age 63.6±0.6) were selected and examined clinically. Bone mineral density (BMD) of the lumbar spine (n=18) and forearm (n=17) was determined by dual energy X-ray absorptiometry. All subjects in group O were of average build, but they had low BMD (percentage to peak bone mass: 60.5±1.3%). No significant correlation was found between the BMD level and periodontal clinical parameters in group 0. Numbers of present teeth and percentage of treated teeth were 23.0±1.3, 60.0±4.1% in group 0, 22.6±1.5, 53.2±6.2% in group P, respectively, Percentage of periodontally diseased teeth and bleeding on probing were 46.2±6.3%, 37.5±4.2% in group O and 39.6±6.3%, 24.6-±-4.4% in group P, respectively. Periodontal conditions in group O were more severe than those in group P. These results suggest that severe osteoporosis may be associated with periodontal breakdown, but further investigation will be necessary.